TiO2 nano-coated thin film PV glazing with superior thermal resistance, self-cleaning, electricity generation and adaptive optical control. (23rd December 2021) - Cuce, Erdem; Cuce, Pinar Mert; Riffat, Saffa
Abstract: A unique nano-coated photovoltaic (PV) glazing technology with superior multifunctional features, thermally resistive PV glazing (TRPVG), is introduced, and for three different configurations of TRPVG (TRPVG-Air12, TRPVG-Ar12, TRPVG-Ar16), UVC/UVA absorption, noise reduction, thermal insulation, electricity generation, visible light and solar radiation control are evaluated through an extensive experimental methodology. Energy production and acoustic tests are conducted in a simulation house, whereas the rest of the experiments are carried out under real operating conditions. The results reveal that each sample is capable of blocking 100% of incoming UVC and UVA light. Visible light control of TRPVG-Ar12 (Glass 1) is found to be 94.4%, whereas it is 88.9% for TRPVG-Air12 (Glass 2) and 93.6% for TRPVG-Ar16 (Glass 3). Solar radiation blockage of Glasses 1–3 is found to be 93.5%, 90.9% and 94.8%, respectively. Average temperature difference between front and rear glazing is determined to be 21.3°C, 19.9°C and 21.7°C for Glasses 1, 2 and 3, respectively. A total of 25 independent acoustic tests are performed for Glass 3, and the sample is observed to reduce 33% of outdoor noise in dBA. Solar simulator tests reveal that Glass 3 can generate 102.6 W of electricity per square metre of PV module area.